Artificial and Biological Neurons: Interdisciplinary Issues and Future Perspectives. White Paper (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Recent developments in the technological domain have increased the interactions between artificial and natural spheres, leading to a growing interest in the ethical, legal and philosophical implications of AI research. The present paper aims at creating an interdisciplinary discussion on issues raised by the use and the implementation of artificial intelligence algorithms, robotics, and applied solutions in the neuroscience and biotechnology field. Building on the findings of the webinar "Workshop neuroni artificial e biologici: etica e diritto", this work explores the issues discussed in the workshop, it attempts to show both the existing challenges and opportunities and it seeks to propose ways forward to overcome some of the investigated problems.
Keywords: AI systems; organoids; ethical and legal issues; trustworthiness; interdisciplinarity